Investigation Methodology of a Virtual Desktop Infrastructure for IoT - Doowon Jeong; Jungheum Park; Sangjin Lee; Chulhoon Kang (Journal of Applied Mathematics)
Cloud computing for IoT (Internet of Things) has exhibited the greatest growth in the IT market in the recent past and this trend is expected to continue. Many companies are adopting a virtual desktop infrastructure (VDI) for private cloud computing to reduce costs and enhance the efficiency of their servers. As a VDI is widely used, threats of cyber terror and invasion are also increasing. To minimize the damage, response procedure for cyber intrusion on a VDI should be systematized. Therefore, we propose an investigation methodology for VDI solutions in this paper. Here we focus on a virtual desktop infrastructure and introduce various desktop virtualization solutions that are widely used, such as VMware, Citrix, and Microsoft. In addition, we verify the integrity of the data acquired in order that the result of our proposed methodology is acceptable as evidence in a court of law. During the experiment, we observed an error: one of the commonly used digital forensic tools failed to mount a dynamically allocated virtual disk properly.